Comparison of cardiorespiratory resistance in different menstrual cycle phases in female futsal players - Nabo, J.; Conceição, A.; Parraca, J. A.; Tomas-Carus, P.; Batalha, N. (Apunts Sports Medicine, 2021)
Introduction: This study was aimed to investigated and compare the cardiorespiratory resistance of futsal players during the follicular and luteal phases of the menstrual cycle. Material and methods: Fourteen female players (age: 24.1 ± 4.1 years; body mass: 59.6 ± 9.1 kg; height: 1.64 ± 0.06 m; index body mass: 22.1 ± 2.8 kg/m2) were submitted to a cardiorespiratory resistance test, that was performed in a calibrated treadmill, where we had as reference for the calculation of VO2max. Each subject also performed two evaluations of the intended test, corresponding to the phases of the menstrual cycle: folicular phase (day 8 ± 3) and luteal phase (day 20 ± 2). Results: The results of the present research showed that there were significant changes, showing higher values of the cardiorespiratory resistance in luteal phase (VO2max = 41.199 ml/kg/min) compared to folicular phase of the menstrual cycle (VO2max = 39.030 ml/kg/min), where p = 0.043. There is still a great deal of controversy in the existing literature when considering a relationship of menstrual cycle phases to physical exercise. Conclusion: The cardiorespiratory resistance of futsal players was increased in luteal phase compared to follicular phase, and management of the training is advisable, namely in type and volume.